2010
DOI: 10.1007/s11738-010-0559-x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of ploidy and homozygosity of carrot plants obtained from anther cultures

Abstract: The purpose of the present work was to evaluate carrot plants obtained from anther cultures with respect to their ploidy and homozygosity. Ploidy was determined using flow cytometry. Homozygosity of analyzed plants was determined using isoenzymes, glucose-6-phosphate isomerase (PGI) and aspartate aminotransferase (AAT). The cytometric tests revealed that more than 90% of the carrot plants obtained from anther cultures were doubled haploid. In the initial assessment of polymorphism of the two enzymatic systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 19 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…In another study, regenerants obtained in a culture of isolated microspores had an SHGD rate ranging from 17.5% to 63.6% depending on carrot accession [37]. A total of 90% of carrot regenerants obtained from another culture were diploid [38]. The flow cytometric analysis of carrot plants obtained in an in vitro culture of unfertilized ovules in carrot showed that 97.7% of the regenerants were diploid [39].…”
Section: Spontaneous Haploid Genome Doubling In Vegetable Cropsmentioning
confidence: 95%
“…In another study, regenerants obtained in a culture of isolated microspores had an SHGD rate ranging from 17.5% to 63.6% depending on carrot accession [37]. A total of 90% of carrot regenerants obtained from another culture were diploid [38]. The flow cytometric analysis of carrot plants obtained in an in vitro culture of unfertilized ovules in carrot showed that 97.7% of the regenerants were diploid [39].…”
Section: Spontaneous Haploid Genome Doubling In Vegetable Cropsmentioning
confidence: 95%
“…The ploidy of the acclimatized plants was determined by an indirect method involving measurements of the amount of nuclear DNA with a flow cytometer as described by Kiszczak et al [15] and by following a modified version of Galbraith's procedure [22]. The analysis was conducted with the use of a Partec CA-II flow cytometer (Partec GmbH, Germany).…”
Section: Assessments Of Ploidy and Homozygositymentioning
confidence: 99%
“…The analysis of homozygosity of the donor plants and DH lines was performed using two isoenzymes, phosphoglucose isomerase (PGI, EC 5.3.1.9) and aspartate aminotransferase (AAT, EC 2.6.1.1), following the extraction protocol described by Kiszczak et al [15]. Electrophoresis was performed in 10% starch gel as described by Gottlieb [23].…”
Section: Assessments Of Ploidy and Homozygositymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, this method is non-destructive and only requires a small amount of tissue (Doležel 1997). Flow cytometry is a very successful and convenient method for analyzing ploidy level and/or estimating genome size in many plant species (Obidiegwu et al 2009(Obidiegwu et al , 2010Ono and Hosaka 2010;Schlaepfer et al 2010;Kiszczak et al 2011;Kumar et al 2011;Burson et al 2012;Scaldaferro et al 2012;Angeles et al 2013;Moon et al 2013).…”
Section: Introductionmentioning
confidence: 99%